ANALISIS METODE BRAINSTORMING DALAM KEMAMPUAN BERPIKIR KRITIS PADA MATA KULIAH LANDASAN PEDAGOGIK MAHASISWA PGSD - Rizka Novi Irmaningrum; Oriza Zativalen; M. Arif Nur Hidayat (Program Studi PGSD, FKIP, Universitas Mataram, 2023)
In pedagogic foundation courses there are still many students who have not been able to achieve critical thinking skills in dealing with problems according to the pedagogic foundation material. Based on this, it is necessary to have an appropriate learning method. The formulation of the problem in this study is how to analyze the brainstorming method in critical thinking skills in the pedagogical foundation course of PGSD students. The purpose of this study was to determine the analysis of the brainstorming method in critical thinking skills in the pedagogical foundation courses of PGSD students. The subjects of this study were second semester students of PGSD S1 Muhammadiyah University of Lamongan. The research method used is a qualitative method with a descriptive design. The research results obtained from interviews, observations, questionnaires and documentation studies in second semester PGSD students that the application of the brainstorming method in pedagogic foundation courses is able to develop students' critical thinking skills as seen by the presence of various creative ideas conveyed in the lecture process in class. Students are given wider opportunities to convey their ideas without limits on various problems in pedagogical foundation courses. The brainstorming method can develop a scientific attitude and better student creativity. The results of the observations also showed that all the ideas presented were well received and together they sought the right solutions for the basic pedagogic problems that arose during the discussions. It can be concluded that the application of the brainstorming method in pedagogical foundation lectures can develop students' critical thinking skills and scientific attitudes.